126 Randomized Controlled Trial of Day-Care and Hospitalized Management of Severe Pneumonia with Severe Acute Malnutrition in Children in Bangladesh. (October 2012) - Ashraf, H; Alam, NH; Gyr, N
Abstract : Background and aims: Severe childhood pneumonia and severe acute malnutrition (SAM) require hospitalized management but inadequate pediatric beds limits hospital-care in Bangladesh. As two prospective observational studies showed that day-care facility-based management of severe pneumonia and SAM were successful as alternatives to hospitalization, a RCT was conducted. Methods: A randomized hospital (ICHSH) versus day-care (The Radda Clinic equipped with oxygen, suction, pulse oximeter, nebulizer, glucometer) comparative study was carried out to evaluate the safety and effectiveness of day-care model. Children aged 2–59 months having severe pneumonia with SAM were randomized to day-care or hospital-care. Parents brought children at 08:00 at day-care clinic and back home at 17:00 daily after receiving antibiotics, diet, micronutrients and oxygen. For hospital-care, children received similar 24-hour treatment with antibiotics, diet, micronutrients and oxygen daily. Both day-care and hospital management continued daily until improvement and discharged. Results: In total, 340 children were randomized to either day-care or hospital-care management. Successful management was possible in 136/170 [80% (95% CI 73.4–85.3%)] day-care children and 144/170 [84.7% (95% CI 78.5–89.3%)] hospital-care children. Of remaining 34 day-care children, 29 [17.1% (95% CI 12.1–23.4%)] were referred to hospital and 5 [2.9% (95% CI 1.3–6.7%)] discontinued treatment. Of remaining 26 hospital-care children, 18 [10.6% (95% CI 6.8–16.1%)] were referred to specialized hospitals and 6 [3.5% (95% CI 1.6–7.5%)] discontinued treatment. Conclusion: Children with severe pneumonia with SAM could be treated safely and effectively on a day-care basis at established day-care clinics, similar to hospital management, if required logistic support is available.